2020
DOI: 10.3390/jcm9092944
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Novel Myositis Autoantibodies in a Large Cohort of Patients with Interstitial Lung Disease

Abstract: Connective tissue diseases (CTDs) are an important secondary cause of interstitial lung disease (ILD). If a CTD is suspected, clinicians are recommended to perform autoantibody testing, including for myositis autoantibodies. In this study, the prevalence and clinical associations of novel myositis autoantibodies in ILD are presented. A total of 1194 patients with ILD and 116 healthy subjects were tested for antibodies specific for Ks, Ha, Zoα, and cN1A with a line-blot assay on serum available at the time of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Moreover, two-thirds of the patients had autoantibodies against anti-Ro52, which has been previously reported to co-exist with other antisynthetase autoantibodies and more severe ILD (135,136). A more recent study reported the prevalence of anti-Zo autoantibodies as 1.4% in patients with ILD and novel associations of anti-Zo with connective tissue-disease related ILD (CTD-ILD) and idiopathic pneumonias (45).…”
Section: Asparaginyl-trna Synthetasementioning
confidence: 87%
See 1 more Smart Citation
“…Moreover, two-thirds of the patients had autoantibodies against anti-Ro52, which has been previously reported to co-exist with other antisynthetase autoantibodies and more severe ILD (135,136). A more recent study reported the prevalence of anti-Zo autoantibodies as 1.4% in patients with ILD and novel associations of anti-Zo with connective tissue-disease related ILD (CTD-ILD) and idiopathic pneumonias (45).…”
Section: Asparaginyl-trna Synthetasementioning
confidence: 87%
“…The first report of autoantibodies against TyrRS referred to as anti-YRS or anti-HA was published in 2005 in a patient with ASSD features (17). The prevalence of anti-HA autoantibodies in a large cohort of patients with ILD (n = 1,194) was 2% (45).…”
Section: Tyrosyl-trna Synthetasementioning
confidence: 98%
“…The fact that we used population controls that might have other autoimmune diseases could explain some of the reactivities. Recent studies reported a relatively high prevalence of anti-Zo, -KS, and -HA in a broad spectrum of ILD patterns [42], and ILD has been reported as the primary clinical feature of anti-KS patients [43]. In our cohort, ten patients with IIM were identified with these autoantibodies, and ILD was reported only in three.…”
Section: Discussionmentioning
confidence: 57%
“…anti-Zo, Ks and Ha, has contributed to shed a new light in the comprehension of ASS. ILD seems to be one of the most common feature in anti-Ks and anti-Ha positive patients [ 18 , 19 ], in whom lung involvement may be the sole manifestation of ASS and present with NSIP pattern and long-term stabilization of lung functionality [ 20 ]. Conversely, in case of anti-Zo, ILD, arthritis and myositis are reported in similar percentage [ 21 , 22 ], but data are restricted to a dozen of patients [ 21 – 24 ].…”
Section: Discussionmentioning
confidence: 99%